PENINGKATAN KEPEDULIAN LINGKUNGAN SISWA SDN TANJUNG 1 MELALUI KEGIATAN DAUR ULANG SAMPAH ANORGANIK - Indah Shofiatin; Hikmah Labibah; Mohammad Iqbal Faqih; Cindy Nur Miristianti; Nilam Larassati; Ika Dian Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to increase environmental awareness of students at SDN Tanjung 1 through inorganic waste recycling activities. The main problem raised in this study is the low awareness of students towards the importance of maintaining environmental cleanliness, especially in the management of inorganic waste which is often ignored. The method used in this study is a descriptive method with a qualitative approach. The subjects of the study were students in grades IV and V who were involved in recycling craft activities by utilizing inorganic waste such as plastic bottles, cardboard, and food wrappers. The activities were carried out in several stages, namely counseling, observation, the process of making the work, and presentation of the results. The results of the study showed that students were not only able to produce creative and functional recycled works, but were also able to explain the benefits of the work for the environment, such as reducing waste and preventing pollution. Aspects of creativity, neatness, accuracy of material use, and efficiency of work time also showed significant development. In addition to skills, this activity also formed students' attitudes of responsibility and concern for environmental preservation. The conclusion of this study is that inorganic waste recycling activities are effective in increasing students' environmental awareness holistically.